The Impact of Math Manipulatives as a Multi-Sensory Teaching Technique in Statistics - Danri Delport (MUST: Journal of Mathematics Education, Science and Technology, 2021)
Many students in social sciences have negative attitudes towards statistics courses, which are often excessively rigid, abstract, and employing teaching approaches that take much of the fun out of learning.  A great deal of research has shown that the human brain learns and performs better in situations where information is integrated across several sensory modalities.  Research also shows how multisensory teaching approaches are valuable in the learning of language and literacy, as well as for children with learning disabilities like dyslexia. Furthermore, many research studies have pointed out how math manipulatives contribute to students’ experiences by providing them with hands-on and concrete learning experiences.  Currently, there seems to be a lack of research that incorporates math manipulatives as a multisensory teaching technique in introductory statistics courses.  The purpose of this research is to investigate whether the use of math manipulatives as a multisensory teaching technique has an impact on students' academic performance in Statistics II at a South African university.  A non-equivalent pretest posttest design was employed to see if the posttest performance of students exposed to the multisensory teaching strategy (in Statistics II) differed from that of students who received traditional instruction (in Business Statistics).  The results of the study showed that students who were exposed to the multisensory teaching technique using math manipulatives achieved higher scores in Statistics II (µ = 70.18) than the students who were taught through traditional instruction (µ  = 56.56).  The study has significant implications on education, specifically for introductory statistics and probability.